Evaluation of Selenoprotein Supplementation on Digestibility, Growth, and Health Performance of Pacific White Shrimp Litopenaeus vannamei - Rafi Kemal; Ichsan Achmad Fauzi; Sri Nuryati; Wira Wisnu Wardani; Muhammad Agus Suprayudi (Aquaculture Nutrition)
Selenoprotein is a feed additive that can overcome oxidative stress in intensive Pacific white shrimp (Litopenaeus vannamei) culture. This study evaluated the effects of selenoprotein supplementation at various doses on Pacific white shrimp’s digestibility, growth, and health performance. The experimental design used was a completely randomized design consisting of four feed treatments, namely, control and treatments with selenoprotein supplementation of 2.5, 5, and 7.5 g kg feed-1 with four replications. Shrimps (1.5 g) were reared for 70 days and challenged for 14 days by the bacteria Vibrio parahaemolyticus (107 CFU mL-1). Shrimps used in the digestibility performance evaluation (6.1 g) were reared until sufficient quantities of feces were collected for analysis. Shrimp supplemented with selenoprotein exhibited superior digestibility, growth, and health performance compared to the control (P<0.05). The use of selenoprotein at a dose of 7.5 g kg of feed-1 (2.72 mg Se kg of feed-1) was considered the most effective for increasing productivity and preventing disease attacks in intensive shrimp culture.